Análisis cualitativo de algunos modelos en epidemiología matemática a partir del modelo de Kermack-McKendrick (2023)
It is known that we are currently going through a pandemic, which is why it is extremely important to model the behavior of disease transmission, in this paper we intend to analytically address some models based on the Kermack-McKendrick model, which is a system composed of three connected nonlinear ordinary differential equations, which is a well-planned system to be mathematically acceptable and serves to detect parameters that allow taking respective measures to control diseases.